Air Pollution and Entrepreneurship - Liwen Guo; Zhiming Cheng; Massimiliano Tani; Sarah Cook; Jiaqi Zhao; Xi Chen (Institute of Labor Economics (IZA), 2023)
We investigate the effect of exposure to air pollution on an individual's likelihood towards entrepreneurship using panel data in China. To address omitted variable bias and endogeneity arising from self-selection into entrepreneurship and location choice, we employ an individual fixed effects model with an instrumental variable approach. Our findings show that individuals exposed to higher levels of air pollution are less likely to become entrepreneurs or diversify their entrepreneurial activities. Specifically, a one standard deviation increase in air pollution leads to a 21 percentage points decrease in the propensity for entrepreneurship and a 34 percentage points decrease in the likelihood of entrepreneurial diversification. Our study identifies potential channels through which air pollution impacts entrepreneurship. In addition, our findings reveal that air pollution has a more significant negative impact for older individuals, people residing in less populated areas, and those with lower education levels compared to their counterparts.
Keywords: J24; L26; Q53; 330; air pollution; entrepreneurship; China